Behavioural Responses in Pigs administered with Ascorbic acid and Transported by Road for Eight Hours during the Harmattan Season - Yahaya Adeshina Adenkola (Veterinary World, 2011)
Experiments were carried out with the aim of investigating the modulatory role of ascorbic acid (AA) on responses to 8-h road transportation, covering a distance of 260 km at a speed of 40 - 50 km/h, during the harmattan season. Twentynine adult local pigs aged 9 - 12 months served as subjects. Seventeen pigs administered with AA, prior to the transportation, at the dose of 250 mg/kg orally and individually served as experimental animals, and 12 others administered orally with sterile water were used as control animals. The behavioural activities of pigs which included resting (that is, either lying down or standing idle), defaecating, urinating, sniffing, threats of attack (fight), attempts to escape, mounting on one another, hurdling together and routing the floor were monitored with the aid of a video camera without the pigs knowing that they were being observed. Recordings were done based on the number of pigs found performing each activity within 30 min of direct observation, alternated by 30 min of rest and this continued for a period of 4 h. The tape was later watched, analysed and the number of pigs exhibiting each behavioural activity was recorded. Post-transportation, the behavioural activities of standing (94.1 ± 5.8 %), aggressiveness indicated by the percentage of pigs involved in fighting (23.5 ± 6.00 %) and attempts to escape (66.67 ± 14.21 %) were higher in experimental pigs (P< 0.05) post-transportation than control pigs with the corresponding values of 25.00 ± 3.00 %; 0.00 % and 35.29 ± 11.95 %, respectively. The results showed that road transportation induced considerable behavioural stress resulting in depression of the central nervous system. AA administration pre-transportation reduced the manifestation of stressful behavioural activities in experimental pigs following road transportation. In conclusion, long-term road transportation of pigs during the harmattan season induces behavioural stress, alleviated by AA administration. [Vet. World 2011; 4(8.000): 353-357]